Pengaruh Pelatihan “Baturaja Risk Containment” Terhadap Kompetensi Dan Kinerja Karyawan PT.Semen Baturaja (Persero) Tbk. (Studi pada Karyawan Division Produksi) - safar udin (Jurnal DinamikA, 2021)
This study aims to describe various analyzes on the implementation of training activities entitled "Baturaja Risk Containment" which includes aspects of training methods and training materials on changes in competence and changes in employee performance at PT Semen Baturaja (Persero) Tbk, especially in the operating division work unit. Partially this research will describe various analyzes among research variables, among others; describes the analysis of the effect of training methods on employee competencies; describes the analysis of the effect of training materials on employee competencies; describes the analysis of the effect of training methods on employee performance: training materials on employee performance, and describes the analysis of the influence of competence on employee performance. This research is an explanatory research carried out in the operations division. With primary data obtained from questionnaires distributed to employees totaling 58 people. This study applies data analysis methods in the form of descriptive statistical analysis methods and path analysis methods. The results of the analysis in this study show that there is a partially significant effect between 1) training methods and 2) training materials on employee competencies; Furthermore, the analysis in this study also shows that there is a partially significant effect: between 1) training methods, 2) training materials 3) competence on employee performance.